Comparative Analysis of the EF-1? Intergenic Region in Babesia divergens Isolates: Insights into TA Repeat Variation and Potential Regulatory Implications - Ozubek, Sezayi; Sanchez-Flores, Alejandro; Montero, Estrella; Alzan, Heba; Suarez, Carlos E.; Grande, Ricardo; Gonzalez, Luis Miguel (Mdpi, 2026)
Babesia divergens, a zoonotic tick-borne pathogen, causes bovine and human babesiosis in Europe. The Elongation Factor 1 alpha (EF-1 alpha) protein is important in many cellular processes and has emerged as a possible target for subunit vaccine development against parasitic infections, and its intergenic region (IG) is an important tool for genetic manipulation of Babesia parasites. While the EF-1 alpha locus of B. divergens has been described, structural variation between isolates was poorly defined. In order to fill this gap, we performed a comparative analysis of the EF-1 alpha-IG in B. divergens human (Rouen 87 and Spanish sample) and bovine (T & uuml;rkiye) host isolates. Our findings revealed both conserved and variable elements, particularly in TA nucleotide repeat numbers and IG sequence length. The Spanish isolate exhibited the highest TA repeat expansion, whereas the Rouen 87 strain had the shortest IG. Given the known role of repeat-rich promoter elements in gene regulation, these differences may influence EF-1 alpha transcription. Additionally, these findings provide insights into the evolutionary divergence of B. divergens and its host adaptation mechanisms. This study establishes a foundation for future gene editing and transfection strategies, where selecting intergenic sequences with varying TA repeats could optimize transfection efficiency and explain phenotypic differences between isolates from different hosts or regions.
Keywords: Babesia divergens; comparative analysis; Elongation Factor 1 alpha (EF-1 alpha); host range